The Subtle Mechanism of Nickel-Photocatalyzed C(sp3)–H Cross-Coupling - Sharma, Akhilesh K.; Maseras, Feliu (Inorganic chemistry, 2024)
This computational study revises and reformulates the mechanism for the cross-coupling reaction between chlorobenzene and tetrahydrofuran catalyzed by a Ni complex with the assistance of an Ir photocatalyst. This is a representative process of transition-metal photocatalysis, and variations of it have been reported by different experimental authors. It has been also the subject of previous computational studies, which we revise and extend. Density functional theory (DFT) calculations and microkinetic modeling indicate that the most efficient mechanism takes place through an energy-transfer step and involves a NiIII complex.